2014
DOI: 10.1097/ta.0000000000000229
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of ventilation-induced lung injury in a rodent model by inhibition of inhibitory κB kinase

Abstract: IKK may be a therapeutic target for VILI. An IKK inhibitor, IKK 16, can dampen VILI in rats. The beneficial effect of the IKK 16 may be mediated through the inhibition of NF-κB pathway and up-regulation of nuclear factor E2-related factor 2-regulated heme oxygenase 1 through the activation of the phosphatidylinositol 3 kinase/Akt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…It is also known that patients ventilated with high tidal volumes are at risk for VALI and a higher mortality rate (12,17). Although it is unclear precisely how mechanical stretch may induce lung injury, mechanisms that promote the release of inflammatory mediators including TNF-α, IL-1β, IL-8 and HMGB 1 been implicated (8,12,18). An administration of drugs with anti-inflammatory features has shown a decrease in VILI (12,19,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also known that patients ventilated with high tidal volumes are at risk for VALI and a higher mortality rate (12,17). Although it is unclear precisely how mechanical stretch may induce lung injury, mechanisms that promote the release of inflammatory mediators including TNF-α, IL-1β, IL-8 and HMGB 1 been implicated (8,12,18). An administration of drugs with anti-inflammatory features has shown a decrease in VILI (12,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor (NF)-κB is required for maximal transcription of various cytokines, including tumor necrosis factor (TNF)-α, interleukin (IL)-8, and IL-1β (6,7). Furthermore, it has been suggested that inhibitors of NF-κB function may be useful as anti-inflammatory agents (8).…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have shown that Akt negatively regulates p65 transactivation induced by activation of receptors that recognize either extracellular or intracellular bacterial products (53,54). In addition, the activation of Akt by IKK16 has been recently reported in sepsis (12) and lung injury (13). Overall, these data suggest a complex cross-talk between the Akt and NF-κB signaling pathways, which still warrants further investigation.…”
Section: K K I N H I B I T I O N I M P R O V E S O R G a N I N J U mentioning
confidence: 81%
“…To gain a better insight into the potential mechanisms involved in the beneficial effects of IKK16, we investigated the effects of IKK16 on the Akt-survival pathway, which is known to confer tissue protection (12,13). In HS-rats, HS did not significantly affect the degree of phosphorylation of Akt in either kidney or liver compared with sham-operated rats (Figures 8A, B).…”
Section: Effects Of Ikk16 Treatment On Akt Survival Pathwaymentioning
confidence: 99%
See 1 more Smart Citation